Catch Composition of Boat Lift Net at The Fish Landing Base (PPI) Ujong Seurangga Aceh Barat Daya - Hamidi, Hamidi; Isbah, Faliqul; Taufiq, Taufiq (Jurnal Perikanan Terpadu, 2024)
Boat lift net is a fishing gear that is active at night which still widely used in the waters of Southwest Aceh. Fishing with a boat chart requires light as a tow to attract fish to the fishing ground area. Fishermen boats lift net in the waters of Southwest Aceh still use fluorescent lamps (Hannochs). This study aims to determine the types of catches and income of boat lift net fishermen landed at ujong serangga susoh fish landing base, Southwest Aceh. This study used survey methods as well as data collection with interviews and observations. Data analysis is carried out using descriptive and qualitative analysis. The results of the study can be concluded that the type of catch landed at the butt and insect susoh landing base consists of mackerel (Rastrelliger kanagurta) amounting to 87,760 tons, tamban fish (Dussumieria elopsoides) 32,120 tons and anchovies (Stolephorus devisi) 26.440 tons. The highest income was obtained in the type of mackerel amounting to IDR 117.013.333, anchovies IDR 22.840.889 and mining fish IDR 22.840.000 for four weeks of fishing on the boat lift net